2019
DOI: 10.1111/jocn.15035
|View full text |Cite
|
Sign up to set email alerts
|

Catheter dwell time and risk of catheter failure in adult patients with peripheral venous catheters

Abstract: Aims and objectives To explore whether the risk of peripheral venous catheters failure remained constant throughout catheter use in adult patients. Background Peripheral venous catheters, widely used in adult patients, may have a critical threshold dwell time associated with increased risk of catheter failure. Design Prospective, observational study. We have complied with the STROBE checklist of items. Methods This study was conducted from July–October 2018 in Hunan, China. Data on patient factors, catheter fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 31 publications
5
30
3
1
Order By: Relevance
“…Our results also revealed that department was an independent predictor of PVC failure, whereby patients hospitalized on the surgery or emergency internal/surgical ward, mostly suffering from acute pancreatitis, gastrointestinal bleeding, pulmonary infection, multiple trauma, or cerebral hemorrhage, were more likely to experience PVC failure than patients hospitalized on other wards. In accordance with these findings, PVC failure was significantly associated with department (internal medicine, general surgery, orthopedics, gynecology, other surgery) in a previous study 20 of adult patients scheduled for infusion therapy at one of two tertiary hospitals in Hunan China. Patients on surgery or emergency internal/surgical wards often undergo abrupt changes in their clinical status and generally receive large infusions of fluid for fluid replacement and to deliver nutritional elements and medication.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results also revealed that department was an independent predictor of PVC failure, whereby patients hospitalized on the surgery or emergency internal/surgical ward, mostly suffering from acute pancreatitis, gastrointestinal bleeding, pulmonary infection, multiple trauma, or cerebral hemorrhage, were more likely to experience PVC failure than patients hospitalized on other wards. In accordance with these findings, PVC failure was significantly associated with department (internal medicine, general surgery, orthopedics, gynecology, other surgery) in a previous study 20 of adult patients scheduled for infusion therapy at one of two tertiary hospitals in Hunan China. Patients on surgery or emergency internal/surgical wards often undergo abrupt changes in their clinical status and generally receive large infusions of fluid for fluid replacement and to deliver nutritional elements and medication.…”
Section: Discussionsupporting
confidence: 79%
“…This study and others demonstrated that irritant fluid infusion and drugs such as antibiotic use, vasoactive drug use, antihemorrhagic drug use, and dexamethasone use, have an impact on PVC failure. 16,20 High concentrations of irritant fluids and drugs can increase plasma osmotic pressure, cause a fluid shift from within the vascular endothelial cells to the extracellular space, infiltration/extravasation, and vascular stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,8,11 In a study conducted by Miliani et al, 12 a negative correlation was established between the dwell time of catheter and the risk of PVC-related complications. Another study showed that the risk of catheter failure may not remain constant throughout the dwell time, and the risk of PVC failure did not increase after the first 38 h. 13 A recent Cochrane review found no difference in phlebitis and infection risk between routine replacement and clinically indicated removal. 6…”
Section: Discussionmentioning
confidence: 99%
“…3 Different studies showed that complete or partial catheter occlusion affects 16-58% of patients after two years of CVC placement. [4][5][6] The main cause of catheter dysfunction is deep vein thrombosis, the development of fibrin sheaths around the tip of the catheter and/or intraluminal thrombi. 3 The formation of fibrin sheaths occurs between 24 h and 3-7 days of after CVC placement as a result of direct endothelial damage.…”
Section: Introductionmentioning
confidence: 99%